PETROGRAPHIC STUDY ON GENESIS OF SELECTED INERTINITE-RICH COALS FROM JAMBI SUBBASIN - NINING S. NINGRUM; BINARKO SANTOSO (Indonesian Mining Journal, 2009)
Genesis of the coal macerals in the studied area depends particularly on the tectonic and geologic setting. The coals formed in the Jambi Subbasin, which is the back-arc basin associated with the fluvial to deltaic environment results in both rich in vitrinite and inertinite contents. The vitrinite content is associated with the bright lithotype deposited in the wet-swampy area; whereas the inertinite is associated with the dull lithotype deposited in the dry-swampy area. The presence of mineral matter causes the dull lithotype as well. The presence of the liptinite maceral cannot be correlated with the lithotypes. This maceral composition is the extreme phenomenon, because most of the Sumateran coals contain very low inertinite content (<5%) with very high vitrinite content (>80%). The coals contain low ash and low (0.1-0.4%) to medium sulphur (1.3- 1.6%) contents. The above evidence is the answer of the extreme evidence, and this is the objective of presenting this paper. Methods applied in this study include in-situ coal sampling for microscopic analyses, which are petrographic determination and reflectance examination. The samples were also analysed for their proximate according to ASTM (2002).